578. Cost-effectiveness of Infant Vaccination with PCV15 Compared to PCV13 in the United States. (15th December 2022) - Huang, Min; Hu, Tianyan; Weaver, Jessica; Owusu-Edusei, Kwame; Elbasha, Elamin
Abstract: Background: Streptococcus pneumoniae is a major cause of mortality and morbidity in young children. The 13-valent pneumococcal conjugate vaccine (PCV13) has been in routine use in children in the United States (US) since 2010. An investigational 15-valent vaccine (PCV15) that protects against two additional serotypes is currently under review by the FDA. This study aimed to evaluate the clinical and economic impact of routine infant vaccination with PCV15 compared with PCV13 from a US societal perspective. Methods: A Markov decision-analytic model was developed to estimate the impact of PCV15 vs. PCV13 on pneumococcal disease incidence, post meningitis sequalae, and deaths. The model followed the entire US population over a 100-year time horizon, taking herd immunity effects into account. Each vaccination program comprised 3 primary doses and one booster for the new birth cohorts. Model inputs were obtained from the published literature, online databases, and unpublished data. PCV15 effectiveness was extrapolated from observed PCV13 data and PCV7 clinical trials. Costs (in 2021 USD) and quality-adjusted life years (QALYs) were discounted at 3% per year. Because the price for PCV15 in the pediatric indication is currently unknown, an analysis was conducted to determine the threshold price, which was defined as the maximum price for PCV15 to remain cost-saving. A series of sensitivity analyses were performed to test the robustness of model results. Results: The base case results projected that PCV15 prevented 185, 711 more invasive pneumococcal disease cases, 987, 727 all-cause pneumonia cases and 11, 151, 473 pneumococcal acute otitis media and tube-replacement cases compared with PCV13. This resulted in an expected gain of 96, 056 QALYs and total reduction of $7 billion in direct medical costs (excluding vaccine costs), and $4 billion in direct non-medical and indirect costs in the US population over the 100-year time horizon. The threshold price per dose for PCV15 was $28 higher than PCV13's price. Sensitivity analyses showed the results to be robust over plausible values of key model inputs and assumptions. Conclusion: Infant vaccination with PCV15 is projected to provide both clinical benefits and cost-savings compared with PCV13. Disclosures: Min Huang, PhD, Merck & Co., Inc.: full-time employee Tianyan Hu, Ph.D., Merck & Co., Inc.: full time employee Jessica Weaver, PhD, MPH, Merck & Co., Inc.: Employee Kwame Owusu-Edusei, Ph.D., Merck & Co., Inc.: full time employee Elamin Elbasha, Ph.D., Merck & Co., Inc.: full time employee.